Cognitive impairments related to alcohol abuse - Gimzal Gönentür, Aylan; Topçuoğlu, Volkan; Nurmedov, Serdar (Journal of Dependence, 2009)
Alcohol has different levels of impact on memory and other cognivite functions, depending on age, sex, duration and amount of use, nutritional status and individual vulnerability. Alcoholic patients may be unaware of their cognitive deficits due to the possible negative effects of alcohol on executive functions as well as memory. This can prevent alcoholic patients admit with memory-related complaints in early stages. Alcohol use affects central nervous system via direct toxic effects of alcohol and its metabolite acetaldehyde, thiamine deficiency and liver function impairment. DSM-IV covers two diagnoses related to alcohol and cognitive disorders, which are alcohol-induced persisting amnestic disorder and alcohol-induced persisting dementia. However, thiamine deficiency may result with both amnesia and dementia. Moreover, it is not clear if the neurochemical and structural changes in hippocampus and amygdala in Korsakoff syndrome are related to thiamine deficiency or effects of alcohol. Therefore, it is not easy to differentiate between Korsakoff syndrome and alcoholic dementia. It is concluded that alcoholic dementia can be classified under neither cortical nor subcortical dementias, rather it represents clinical symptoms and signs belonging to both types of dementias. This warrants a revision on classification of alcohol-related cognitive disorders. Besides, experience in treatment of alcohol-related cognitive disorders with acetylcholine esterase inhibitors or N-methyl-D-aspartate (NMDA) receptor antagonists such as memantine is limited.